Gel and Molecular Properties of Nonwaxy Rice Starch - Juliano, Bienvenido O.; Perdon, A.A. (Wiley, 1975)
A study of the factors that determine the gel consistency values of nonwaxy milled rice and rice starch showed that these values (in mm) were correlated negatively with the corresponding gel viscosities as measured with a Wells‐Brookfield viscometer. In 6 IRRI rice varieties and an intermediate amylose variety, C 4–63 G, amylopectin contributed more to gel viscosity than did the amylose fraction of the starch. Differences in gel viscosity were observed only at starch concentration of 40 mg in 2 ml 0.2‐N KOH or higher and were not simply related to differences in the intrinsic viscosity [η] of starch. However, gel consistency of starch was significantly correlated negatively with [η] of amylopectin. Gel viscosity was higher in KOH than in potassium acetate but the difference in viscosity was greater for the starch and amylopectin than for amylose.